Lipoic acid-based poly(disulfide)s: Synthesis and biomedical applications - Ivan O. Levkovskyi; Shota Mochizuki; Ajay Zheng; Xiao Zhang; Fuwu Zhang (Nano TransMed)
Biodegradable and adaptable polymeric materials are currently being studied due to their wide scope of potential applications, from nanomedicine to novel multifunctional materials. One such class of polymers are poly(disulfide)s, which contain repeating disulfide bonds in their main chain. Lipoic acid, or thioctic acid, is a biologically derived small molecule containing a 1,2-dithiolane ring capable of undergoing ring opening polymerization to yield poly(disulfide)s. In this review, we highlight the synthesis of lipoic acid-based poly(disulfide)s through thermal and thiolate-initiated ring opening polymerizations, and the development of methodology pertaining to the synthetic methods. We further discuss the biomedical applications of poly(disulfide)s, which have been widely used to construct various responsive biomaterials, including polymer-drug conjugates, nanoparticles, hydrogels, and adhesives.